(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The hypothalamic - pituitary axis is an auto-regulating system that realizes a tight integration among the endocrine, nervous and immune systems. Objective:To identify anatomical and microscopical age changes of hypothalamus-pituitary gland. Methods:Eighteen female rabbits are divided into 3 groups, group A (4-6 months), group B (12-24 months) and group C (36-60 months). The rabbits are sacrificed and dissection of hypothalamus, pituitary gland is done, anatomical position, their weight, measurements and histological study of their sections regarding the number of different cell types. Results:The weight and number of cells in different parts of hypothalamus and pituitary gland are negatively correlated with age. The serum thyroid stimulating hormone (TSH), growth hormone (GH), prolactin hormone (PRL), and adrenocorticotrophic hormone (ACTH) hormones almost remain unchanged while the level of leutinizing hormone (LH) and follicular stimulating hormone (FSH) were increasing with age, and the prolactin hormone level primarily increases with age then decreases with advancing age. Conclusion:The weight of the Hypothalamus and pituitary gland is primarily increased before age of 24 months, and then it started to decrease. The effects of aging inversely on the function and structure of hypothalamus and pituitary gland. Key words:Aging, hypothalamus, pituitary, HPA axis